Meningkatkan Pengalaman Belajar Siswa pada Pendidikan Vokasional: Pengembangan Media Interaktif Pada Mata Pelajaran Praktikum - Thyara Mahanani; Prihastuti Ekawatiningsih (Universitas Negeri Gorontalo, 2024)
This study aims to: 1) Develop learning media in the form of salad making simulation using macromedia flash program, 2) Determine the feasibility of media according to material experts, media experts and students in salad making simulation using macromedia flash program for class X students of SMK PIUS X Magelang. This research was conducted at SMK Pius X Magelang using research and development (R and D) type, with ADDIE development model. The stages in this study consist of; (1) analysis stage; (2) planning stage; (3) development and production stage; (4) implementation trial stage; (5) evaluation stage. To obtain media validation and reliability, it was carried out by 2 material experts and 1 media expert. The instrument trial conducted by 40 students had 2 failed results and 30 were declared valid with a reliability value of 0.921. Data analysis using Descriptive Statistics. The results of the study are as follows: 1) Development of learning media through the Analysis stage: competency analysis, material analysis, student characteristics analysis, instructional analysis. Design: preparation of material framework, determination of systematics, planning of evaluation tools. Develop: pre-research, determination of draft, editing, revision. Implement: product trial. Evaluate. ; 2) for the feasibility of learning media based on material experts in the feasible category with a percentage of 100% and media experts included in the feasible category with a percentage of 96.7%, the results of the instrument feasibility trial included in the very feasible category with a percentage of 53.8%, for the results of media responses by students have a percentage of very feasible 43.7%, feasible 47.5%, less feasible 8.3%, not feasible 0.6%. Based on the results of the pretest 77.2 and posttest 87.2 there was an increase of 10. Thus this media can be said to be feasible for use in Continental learning.